2018
DOI: 10.31393/bba33-2018-8
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of the chest’s size in female volleyball players of different constitutional types

Abstract: During qualified sport selection special attention should be paid to those features and abilities that have a great influence on the effectiveness, and those, that are mainly under the influence of genetic factor. Such morphogenetic markers of sports selection include, firstly, the constitutional features of athletes, in particular the shape of the chest. The purpose of work is to determine the differences between the anthropometric dimensions of the chest between female volleyball players of high level of ath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Chest sizes are one of the most important anthropometric indicators of physical development. These parameters determine not only the somatotypological affiliation of the person, but also play an important role in the prognostic and ascertaining sports selection [24]. Analyzing the age dynamics within the pubertal period of ontogenesis of middle-thoracic diameter, it should be noted that this figure increases sharply in girls 11 years compared with 10 years, during the next calendar age the growth rate of this transverse size of the chest slows down, and at the end of puberty ontogenesis, the size of the middle-thoracic diameter increases sharply, as evidenced by a significant difference found between groups of girls 12 and 13 years.…”
Section: Discussionmentioning
confidence: 99%
“…Chest sizes are one of the most important anthropometric indicators of physical development. These parameters determine not only the somatotypological affiliation of the person, but also play an important role in the prognostic and ascertaining sports selection [24]. Analyzing the age dynamics within the pubertal period of ontogenesis of middle-thoracic diameter, it should be noted that this figure increases sharply in girls 11 years compared with 10 years, during the next calendar age the growth rate of this transverse size of the chest slows down, and at the end of puberty ontogenesis, the size of the middle-thoracic diameter increases sharply, as evidenced by a significant difference found between groups of girls 12 and 13 years.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, to our knowledge, there have been only few studies comparing anthropometric characteristics, such as somatotype and body composition, between female volleyball players and untrained students or young women (Tsunawake et al 2003;Pietraszewska et al 2015;Pastuszak et al 2016;Sarafyniuk et al 2018). These studies have revealed that, compared to students not actively involved in sport activities, volleyball players tended to be taller, while their circumferences of the arm and crus, most of the chest dimensions, body density, and lean body mass exhibited higher values.…”
Section: Introductionmentioning
confidence: 99%
“…The functional state of the central hemodynamics enables the most rapid detection of signs of overwork and overtraining. The peculiarities of the human body structure of the athletes influence the manning of the team, the choice of the tactical drawing of the game in defense and attack, on the definition of training techniques [9,10]. Until recently, the morphological and functional parameters of the athletes' body of sports games were evaluated on average values of parameters: football players, handball players, basketball players.…”
Section: Introductionmentioning
confidence: 99%